The use of digital diplomacy in the diplomatic relations of Costa Rica with other States: challenges and opportunities, in the period of 2010 to 2016 - Moreira Hernández, Alejandra (2017)
This article seeks to analyze the implementation of the new concept of digital diplomacy in diplomatic relations between Costa Rica and Brazil, Chile, Israel and Turkey, in order to show that a good use of these tools can positively impact Costa Rican scope of action in front of the studied countries. Additionally, it see-ks to expose the opportunities and challenges facing the Costa Rica’s Ministry of Foreign Affairs in the use of social networks as media and promotion of foreign policy measures, which now need coordination measures and transparency to disseminate the image desired country.